2010
DOI: 10.14227/dt170210p6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an In Vitro Dissolution Test Method for Inhalation Formulations

Abstract: The aim of this research project was to investigate a potential standardized test method to characterize the dissolution properties of numerous formulation types available for pulmonary delivery. A commercially available dissolution tester was adapted for use as a testing apparatus by the incorporation of a membrane-containing holder. The holder was designed to enclose previously air-classified formulations so that they could be uniformly tested in the dissolution apparatus. Dissolution procedures, the apparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 19 publications
(26 reference statements)
0
67
0
Order By: Relevance
“…Therefore, the Transwell setup was modified by inserting a spacer to lift the inserts, allowing the addition of stir bars. Furthermore, for substance-specific comparison of dissolution profiles, it is mandatory that particle size distribution, amount of drug loading on membrane, and particle distribution on the membrane are similar (8,(11)(12)(13). From Table 4 it can be seen that membrane loading is very similar for PC and PE membranes.…”
Section: Figure 9 Budesonide Dissolution Profiles Using the Pc Membrmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the Transwell setup was modified by inserting a spacer to lift the inserts, allowing the addition of stir bars. Furthermore, for substance-specific comparison of dissolution profiles, it is mandatory that particle size distribution, amount of drug loading on membrane, and particle distribution on the membrane are similar (8,(11)(12)(13). From Table 4 it can be seen that membrane loading is very similar for PC and PE membranes.…”
Section: Figure 9 Budesonide Dissolution Profiles Using the Pc Membrmentioning
confidence: 99%
“…Several dissolution techniques for powders for inhalation have been described, such as the flow-through cell (7)(8)(9), the Franz diffusion cell (8)(9)(10), and the paddle apparatus equipped with a special sample holder (8,11,12). The common disadvantage of these apparatus is the nonphysiologically large amount of dissolution medium (60-1000 mL).…”
Section: Introductionmentioning
confidence: 99%
“…The paddle apparatus with membrane holder was developed by Son et al (10). The apparatus consists of a vessel with 1 l dissolution medium which is immersed in a water bath (Erweka DT70, Erweka, Heusenstamm, Germany).…”
Section: Paddle Apparatus With Membrane Holdermentioning
confidence: 99%
“…The wax paper pieces were then placed into plastic histology cassettes that were dropped into vessels of a paddle apparatus. More recently, this same research group modified an NGI with removable impaction cups that could then be dropped into the paddle apparatus (58). In the past few months, two separate research groups have demonstrated the use of diffusion apparatus to assess dissolution rates for inhalables.…”
Section: Inhalationmentioning
confidence: 99%